Environnement : la gouvernance par la responsabilité ? - Denis Salles (VertigO)
Due to their specificity, environmental problems are difficult to govern using standard politics. The transgression of the traditional political scale, the intersectorial nature of the problems, and the desynchronization of the impact of human activity on the environment, have resulted in the emergence of policies that champion co-responsibility (inter-territorial, intersectorial, intergenerational). This tendency is evidenced by politics which reinforce explicit interdependencies between territories, and by devices which serve to make social actors aware of their responsibilities (in regards to the environment). These environmental devices represent a new and increasing trend in the regulation of collective environmental problems, in that they place greater emphasis on shifting the social practices of individuals (alternate forms of consumption, travel, etc…). This text exposes these mechanisms aimed at making people more responsible. It explores the range and the limits of environmental governance.